Leadership and Human Resource Management Imperatives in a Hybrid Work Environment - Nair, Anjali (Digital Repository of Theses - SSBM Geneva, 2024)
This research explores a key element of our work environment in the post COVID-19 pandemic, that is hybrid working, its challenges and the impact it has had on the management side specifically on senior people leaders, Firstline people leaders and HR professionals in the Indian IT industry. The objective of this study was to research and understand the management sides’ key challenges and then go on to identify the key skills that each of these roles would need to build or hone further, to effectively tackle these challenges. The hypotheses delved into the challenges that people managers and HR professionals experienced about hybrid work environments and how to go about handling the areas that need change. The findings of this research provide a ready reckoner to organizations that are finding it difficult to manage a hybrid work environment, in the form of top organizational policies that need to undergo change, digital tools required, professional and leadership skill requirements and training and development needs.